1979
DOI: 10.1002/bip.1979.360180410
|View full text |Cite
|
Sign up to set email alerts
|

Single crystals and oriented crystallization of ivory nut mannan

Abstract: SynopsisThe preparation of lamellar single crystals of mannan[poly((l -4)-P-D-mannose)] is described. Electron diffractograms clearly identify the perpendicular orientation of the chain axis with respect to the lamellar surface. Since the degree of polymerization is 40 or less, no conclusion is made as to chain folding. The unit cell corresponds to the mannan I structure derived from x-ray fiber data on oriented algal mannan. The baseplane dimensions found were a = 7.22 8 and b = 8.92 8, and the systematic abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
26
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 21 publications
7
26
0
Order By: Relevance
“…The first sample is a pure mannan I as shown by X-ray powder diffraction and has been used in previous work (3,7). Additionally, a whole ivory nut was mounted on a lathe and turned down into a cylinder for direct insertion in the rotor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first sample is a pure mannan I as shown by X-ray powder diffraction and has been used in previous work (3,7). Additionally, a whole ivory nut was mounted on a lathe and turned down into a cylinder for direct insertion in the rotor.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that these so-called hemicelluloses are oriented parallel to the microfibrils (2) but there is no evidence of mannan crystallization in this natural occurrence. Nevertheless, cellulose microfibrils can be made to serve as a crystallization template for mannan, producing an epitaxial crystallization of the mannan chains with their fibre axes parallel to that of cellulose (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unsubstituted β-1,4-mannan, composed of a main chain of β-mannopyranose residues, is an important structural component of some marine algae (Yamasaki et al, 1998) and terrestrial plants such as ivory nut (Chanzy et al, 2004) and coffee bean (Nunes et al, 2006). It resembles cellulose in the conformation of the individual polysaccharide chains, and is water insoluble.…”
Section: Mannan: Occurrence and Structurementioning
confidence: 99%
“…Corrections were made for Lorentz polarization and for the arcing of the diffraction spots using the relationship F i = Ap tan 28/(1 + cos 28), where A is the cross-sectional area, 8 …”
Section: Measurement Of X-ray Intensitiesmentioning
confidence: 99%